2014
DOI: 10.1007/s10803-014-2113-y
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Job Interview Training in Adults with Autism Spectrum Disorder

Abstract: The feasibility and efficacy of Virtual Reality Job Interview Training (VR-JIT) was assessed in a single-blinded randomized controlled trial. Adults with autism spectrum disorder were randomized to VR-JIT (n=16) or treatment as usual (TAU) (n=10) groups. VR-JIT consisted of simulated job interviews with a virtual character and didactic training. Participants attended 90% of lab-based training sessions and found VR-JIT easy-to-use, enjoyable, and they felt prepared for future interviews. VR-JIT participants had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
258
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(267 citation statements)
references
References 33 publications
8
258
1
Order By: Relevance
“…The intensive challenges during their job interviews caused by social deficits were frequently reported among people with ASD, especially those with Asperger's and high-functioning ASD (Mawhood and Howlin 1999;Smith et al 2014;Strickland et al 2013). Müller et al (2003) indicated that poor interview performances limited job opportunities for people on the spectrum, regardless of their working capability.…”
Section: Internal Challenging Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensive challenges during their job interviews caused by social deficits were frequently reported among people with ASD, especially those with Asperger's and high-functioning ASD (Mawhood and Howlin 1999;Smith et al 2014;Strickland et al 2013). Müller et al (2003) indicated that poor interview performances limited job opportunities for people on the spectrum, regardless of their working capability.…”
Section: Internal Challenging Factorsmentioning
confidence: 99%
“…Positive results showed that youth who completed the training program demonstrated significantly more effective interview skills than those who did not. Another virtual reality program for interview skills training was developed by Smith et al (2014). The research indicated that participants in the treatment group greatly improved more on their interview performance than those in the control group.…”
Section: Assistive Technologymentioning
confidence: 99%
“…In summary, through two decades of research examining the role of VRTs for people with ASD, and the promising results of various studies (Cobb, 2007;Maskey, Lowry, Rodgers, McConachie, & Parr, 2014;Parsons & Cobb, 2011;Parsons et al, 2005Parsons et al, , 2006Smith et al, 2014;2015, Strickland et al, 1996, 2007, 2013, we are well placed to continue investigating further these tools and technologies for this specific user-group. This is especially the case as new technology has since evolved considerably and the nature of VR experiences change.…”
Section: Introductionmentioning
confidence: 99%
“…Authors concluded that VR is effective in the treatment of people with intellectual and multiple disabilities. In [Smith et al 2014], the feasibility of a virtual reality job interview training was evaluated with adults with Autism. Authors conclude that it is an accessible strategy for improving community-based outcomes among people with ASD, and stated VR-based training may be a efficacious tool to improve job interview skills for those individuals.…”
Section: Related Studiesmentioning
confidence: 99%